Isoforma de receptor e canais iônicos responsáveis pela corrente ativada por receptores metabotrópicos de glutamato em neurônios do MNTB - Ana Maria Bernal Correa (2016)
Metabotropic glutamate receptors play physiological roles in the control of neuronal excitability, modulation of synaptic transmission, regulation of synaptic efficacy and development of the nervous system. These receptors can be classified into three groups according to their structure and signaling pathways. Group I is composed of the isoforms mGluR1 and mGluR5 that share genetic sequence similarity, selectivity for certain agonists, and couple through Gq protein and the Phospholipase C / IP3 / DAG pathways. Activation of postsynaptic Group I mGluR receptors generates an inward (depolarizing) current in Medial Nucleus of the Trapezoid Body (MNTB) neurons through an unknown mechanism. This current, which we call ImGluR-I, increases the excitability of these cells. MNTB neurons express both mGluR1 and mGluR5 receptors, however the individual contribution of each isoform to ImGluR-I is unknown. The aim of this study is characterize the contribution of each Group I metabotropic glutamate receptor isoform to the generation of this current and to identify the channel types responsible for this ionotropic action of metabotropic glutamate receptors. Whole-cell current and voltage clamp recording were made from neonatal mice (postnatal days 6-10; weight 3–6 g) MNTB neurons using a brain slice preparation. Drug effects were quantified by measuring the change in membrane potential or membrane current during drug application compared to the previous baseline. Numerical data are presented as mean ± S.E.M. Statistical analysis was performed using Student’s t test with P<0.05 considered statistically significant. This project was approved by CEUA/UFMG (Protocol 159/2015). The Group I mGluR selective agonist DHPG evoked a dose-dependent depolarization of MNTB neurons, with a maximal effect about 8 mV and an EC50 of 1 μM. In voltage clamp recordings, DHPG (10 μM) induced an inward current (-30.4 ± 3.1 pA). MPEP (10 μM), a selective antagonist for mGluR5, reduced ImGluR-I by 40.5 ± 9.2% (P = 0.05, N = 5), whereas LY367385 (100 μM), a selective antagonist for mGluR1, inhibited the inward current by 100% (P = 0.02, N = 3). In a second approach we used mice with targeted deletion of the mGluR5 receptor gene. We observed no difference in ImGluR-I measured in mGluR5 KO mice when compared to WT littermates (-37.7 ± 6.5 pA vs -35.1 ± 5.0 pA, N = 6; P = 0.79). To identify the ionotropic mechanism of ImGluR-I, we tested inhibitors of candidate ion channels. Block of ASIC channels with Amiloride (100 μM) did not inhibit significantly ImGluR-I. In contrast, block of inward-rectifying K+ channels with BaCl2 (500 μM) or block of HCN channels with ZD7288 (100 μM) reduced the current by 33.4 ± 5.9% (P = 0.04, N = 8) and 59.6 ± 7.5% (P = 0.01, N = 6), respectively. When applied together, BaCl2 (500 μM) and ZD7288 (100 μM) inhibited the current by 77 ± 3.3% (P = 0.02, N=4). We concluded that both mGluR1 and mGluR5 contribute to the generation of ImGluR. However, only mGluR1 is essential as block of this isoform abolishes the current and mGluR1 can completely compensate for the loss of mGluR5 in KO animals. Block of HCN channels or inward-rectifying K+ channels strongly reduces ImGluR-I, indicating that these channel types are responsible for the ionotropic effects of metabotropic glutamate receptors in the MNTB.